Founding fathers (History Channel, 2000)
They were the most legendary and respected politicians, statesmen and warriors of history's first republic since the days of ancient Rome. They were also traitors and smugglers, rabble rousers and hot-heads, unfaithful husbands and prodigious drinkers. Our "Founding Fathers" were, in fact, human beings. Gain a fascinating glimpse behind the images on the marble busts and faces on our dollar bills and pocket change.